DANCING WITH THE ELECTRONS: TIME-DOMAIN AND CW IN VIVO EPR IMAGING - Subramanian, Sankaran (2008)
The progress in the development of imaging the distribution of unpaired electrons in living systems and the functional and the potential diagnostic dimensions of such an imaging process, using Electron Paramagnetic Resonance Imaging (EPRI), is traced from its origins with emphasis on our own work. The importance of EPR imaging stems from the fact that many paramagnetic probes show oxygen dependent spectral broadening. Assessment of in vivo oxygen concentration is an important factor in radiation oncology in treatment-planning and monitoring treatment-outcome. The emergence of narrow-line trairylmethyl based, bio-compatible spin probes has enabled the development of radiofrequency time-domain EPRI. Spectral information in time-domain EPRI can be achieved by generating a time sequence of T(2)* or T(2) weighted images. Progress in CW imaging has led to the use of rotating gradients, more recently rapid scan with direct detection, and a combination of all the three. Very low field MRI employing Dynamic Nuclear polarization (Overhauser effect) is also employed for monitoring tumor hypoxia, and re-oxygenation in vivo. We have also been working on the co-registration of MRI and time domain EPRI on mouse tumor models at 300 MHz using a specially designed resonator assembly. The mapping of the unpaired electron distribution and unraveling the spectral characteristics by using magnetic resonance in presence of stationary and rotating gradients in indeed ‘dancing with the (unpaired) electrons’, metaphorically speaking.